EXPLORING DARK DESIRES IN AVENGED SEVENFOLD’S A LITTLE PIECE OF HEAVEN: A PSYCHOANALYTIC AND PHILOSOPHICAL READING - Aljazera, Falah Muzaqqi; Rahayu, Masnia (Universitas Islam Sumatera Utara (UISU), 2025)
Research on dark themes in literature and music often focuses on narrative or aesthetic form, leaving a gap in understanding how psychological and philosophical dimensions shape artistic expression. This study aims to explore how dark desires are represented in Avenged Sevenfold’s A Little Piece of Heaven through psychological, sociological, and philosophical perspectives. Employing a qualitative descriptive method with thematic analysis, the research identifies symbolic patterns of unconscious drives, moral conflict, and emotional duality within the song’s narrative. The analysis applies Freud’s concepts of the id, ego, and superego alongside Jung’s theory of the shadow self to uncover repressed impulses, while Nietzsche’s philosophy is used to interpret how destructive instincts are transformed into creativity and moral reflection. The findings reveal that A Little Piece of Heaven embodies the duality of affection and violence, suggesting that dark desires function as both destructive and creative forces within human consciousness. This study contributes to literary and cultural studies by demonstrating how psychological repression and moral conflict in heavy metal music can be interpreted as a creative articulation of human emotion, offering insight for both literary analysis and cultural pedagogy.